Organização Social de Saúde na Gestão Hospitalar, em Fortaleza: limites e possibilidades - Saboya, Maria Corcyra Vasconcelos de (2015)
This research aims to understand the public health management model, which aims to improve its performance, established in accordance with the administrative reform of 1990 in the neo-liberal conception of state action, which transfers the management of non-exclusive activities for non-profit entities under private law. It is an evaluation research with comprehensive critical approach to in-depth evaluation, using quantitative and qualitative data through techniques such as open interviews, direct observation, in addition to literature research, legislation, documents and electronic sites. This presente work had as design an analysis of the Organização Social de Saúde (OSS), developed in a Public Hospital, by management contract between the Secretaria de Saúde do Estado do Ceará (SESA), Secretaria de Planejamento e Gestão (SEPLAG) and the OSS. In order to understand the management, we analyse reports of the committee of contract evaluation, 2008, 2009, 2012 and 2013, and OSS management reports from 2010 and 2011. According to a survey we have accomplis hed we believe that the management performed in the studied time, is complex and achieved relative effectiveness, since the affected population with public policy received some positive results achieved in results of contractual targets, while others have not been achieved, such as in the case of hospital infection control, over the resoluteness and user satisfaction. The deconcentration of responsibilities was able to achieve some improvement in speed and quality, considering that the hospital model is closed doors and only attends patients referred by Central de Regulação do SUS (CRESUS), however, there is a disrespect to the principle of universality of the Sistema Único de Saúde (SUS) as well as an approach to re-concentration of responsibilities, for the OSS, only enabled, is in charge of one hundred and five health facilities which also removes the assumption of healthy competition reform. We believe that the management of OSS, focusing on results, is developing with difficulties in achieving all set goals. Effective implementation from the State Control is missed with the social control as well as transparency, essential to the achievement of the incentive policy to social organizations. Finally, we made a proposition in order to deploy an integrated system of control to improve health services, arising from contractual goals.